Identification of Hub Genes Correlated with the Initiation and Progression of CKD in the Unilateral Ureteral Obstruction Model - Xinxin Li; Junjie Li; Xiaobing Yao; Jun Yang (Biomedicines, 2025)
Background: Chronic kidney disease (CKD) is a global health problem marked by a persistent deterioration in the function of the nephrons and kidneys. To identify novel therapies for CKD, we investigated the molecular targets associated with the initiation and progression of the disease. Methods: The transcriptional profile dataset of GSE42303 was downloaded from GEO (The Gene Expression Omnibus). Utilizing the R package limma, the differentially expressed genes (DEGs) were identified between control (Con) and unilateral ureteral obstruction (UUO) mice. Then, functional enrichment, protein–protein interactions (PPI) and subsequent hub genes were identified by multiple bioinformatics approaches. Further validations of these hub genes were confirmed through the GSE118339 dataset and in vivo experiments. Results: We found 381 DEGs between Con and UUO mice (308 up-regulated genes and 73 down-regulated genes). GO functions and pathway analysis indicated that DEGs were mainly enriched in activities associated with inflammation and fibrosis. The mRNA expressions of nine hub genes were identified and confirmed by dataset GSE118339 and in vivo experiments. Conclusions: The hub genes Fgg, Penk, Ckap4, and Gpc3 may be new prospective targets for the treatment of the initiation and progression of CKD.